L2 EVIDENCE FOR THE STRUCTURE OF THE L1 LEXICON - Reiss, Charles (International Journal of English Studies, 2001)
In this paper 1 suggest that L2 research could provide answers to questions concerning the structure of L1 grammars that cannot, as a matter of logic, be answered by only examining L1 data and intuitions. In other words, L2 data from an individual P can provide ’external’ evidence bearing on the structure of P’s L1 grammar, Ll,. This type of evidence will be particularly welcome where competing theories of Ll, are extensionally equivalent where they generate the sarne output representations. 1 am proposing, therefore, that L2 research need not restrict itself to maintaining consistency with work in theoretical linguistic modeling. Instead L2 research can itself make unique contributions to the general theory of grammar. In addition to potentially leading to fruitful results, the issues that provide the background to the discussion warrant examination on other grounds, since they help clarifj the goals of linguistic research and the compatibility of various frameworks of linguistic theory with their own stated goals.